Impact of a Stress Management Intervention on Psychological Outcomes of Women Entrepreneurs in Ethiopia - Hailemichael, Adiam; Kalra, Naira; Hailemichael, Adiam; Habtamu, Kassahun; Selamu, Medhin (2023)
Adiam Hagos Hailemicheal, Africa Gender Innovation Lab, World Bank Group Research team: Naira Kalra, Adiam Hagos Hailemicheal, Kassahun Habtamu and Medhin Selamu REGIONAL WORKSHOP SPIR II Learning Event Co-organized by IFPRI, USAID, CARE, ORDA, and World Vision MAY 16, 2023 - 9:00AM TO MAY 17, 2023 - 5:00PM EAT